The techlash and tech crisis communication - Weiss-Blatt, Nirit (Emerald Publishing Limited, 2021)
This book provides an in-depth analysis of the evolution of tech journalism. The emerging tech-backlash is a story of pendulum swings: we are currently in tech-dystopianism after a long period spent in tech-utopianism.